2013
DOI: 10.1371/journal.pone.0058204
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Fecal Volatile Organic Metabolites in Irritable Bowel Syndrome

Abstract: Diagnosing irritable bowel syndrome (IBS) can be a challenge; many clinicians resort to invasive investigations in order to rule out other diseases and reassure their patients. Volatile organic metabolites (VOMs) are emitted from feces; understanding changes in the patterns of these VOMs could aid our understanding of the etiology of the disease and the development of biomarkers, which can assist in the diagnosis of IBS. We report the first comprehensive study of the fecal VOMs patterns in patients with diarrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
158
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(171 citation statements)
references
References 50 publications
6
158
2
5
Order By: Relevance
“…They demonstrated significant differences between active CD vs. IBS and IBS vs. HC (Table 3). Both the sensitivity and specificity for the discrimination of IBS from HC and IBS from IBD are in line with a previous conducted study by Ahmed et al [33].…”
Section: Inflammatory Bowel Disease and Irritable Bowel Syndromesupporting
confidence: 91%
See 1 more Smart Citation
“…They demonstrated significant differences between active CD vs. IBS and IBS vs. HC (Table 3). Both the sensitivity and specificity for the discrimination of IBS from HC and IBS from IBD are in line with a previous conducted study by Ahmed et al [33].…”
Section: Inflammatory Bowel Disease and Irritable Bowel Syndromesupporting
confidence: 91%
“…In 2013, Ahmed et al compared fecal VOCs of 30 diarrhea-predominant adult IBS patients to 110 adult IBD patients by means of GC-MS [33]. They found that three types of VOCs were more abundant in the IBS group, while the abundance of five types of VOCs were higher in the IBD group (Table 3).…”
Section: Inflammatory Bowel Disease and Irritable Bowel Syndromementioning
confidence: 99%
“…[15][16][17][18][19] Some of the proposed biomarkers (which are unfortunately not widely available) may also serve as therapeutic targets and enhance outcomes. Despite this, a systematic review and meta-analysis that evaluated all generally available approaches to diagnose IBS demonstrated that biomarkers alone performed similarly to symptom-based criteria, 20 while adding to the cost of care.…”
Section: Irritable Bowel Syndrome (Ibs) Is a Chronic Functional Gastrmentioning
confidence: 99%
“…The many types and quantities of headspace VOCs released from fecal samples reflect the overall metabolic state of an individual which may be affected by a wide variety of factors that alter intestinal metabolism including diet, medication and drug use, ingestion of probiotics and antibiotics, as well as types of gastrointestinal resident microbes (GIRMs) present which comprise the GI-microbiome, and presence of disease states in the body [8,9]. Consequently, alterations in metabolism caused by GI-tract infections, inflammation, and related disease states can result in significant changes in GIRMcomposition, altering the complex mixture of VOCs gases released in fecal samples.…”
Section: Mechanisms and Theory Of Gastrointestinal-disease Detectionmentioning
confidence: 99%
“…For GI diseases, analysis of VOCs emitted from fecal samples have shown significant changes in VOC profiles that have helped in disease etiology and identification of disease biomarkers associated with specific diseases [8]. Changes in VOC profiles of the GI-tract, resulting from alterations in host physiology due to disease processes (pathogenesis), also often cause changes in gut microbiota composition due to changes in GI-growth conditions for microbes in diseased patients compared with healthy controls.…”
Section: Mechanisms and Theory Of Gastrointestinal-disease Detectionmentioning
confidence: 99%